Analysis of The Effectiveness of Integrated Information System Implementation (Case Study: PT Samudera Mulia Abadi Tbk) - Anneke Wangkar (Eduvest - Journal of Universal Studies, 2023)
Entering the era of information and free trade, PT. Samudera Mulia Abadi requires a certain advantage in order to face national and international competition. For this reason, every company strives to provide the best service facilities for customers through the accuracy, precision and effectiveness of information. These things must be supported by the development of information technology at this time. An organization that has a well-designed information system will generally have a competitive advantage over an organization with a weaker system. However, the facts show that the implementation of an information system is not easy. The more departments related to the information system, the more complex the information system will be and the higher the risk of failure. This research takes a case study of the effectiveness of information system implementation at PT Samudera Mulia Abadi (SMA) and what factors influence it. The method use in this study is a survey method by distributing questionnaires to all respondents who use an integrated information system at PT SMA. From the research results, it was found that several factors influence the effectiveness of information system implementation, including : user interaction with information systems, IT support, involvement of consultants and features of information  systems. Without the above factors, it is very unlikely that companies that implement integrated information systems can take maximum advantage of integrated information systems that are applied to their companies